(untitled) (Far Western Review, 2024)
This study assessed avian diversity and composition on bamboo clumps across different habitats in Rong Rural Municipality and Mechinagar Municipality, eastern Nepal. To determine bird diversity associated with bamboo and to understand the contribution of bamboo to avian diversity, pointcount method was used to collect data and analyzed by using MS Excel 2019.Atotal of39 species having 255 individuals from 28 families and 8 orders were observed on bamboo clumps. Amongst them 28 identified species of birds, 199individuals belonged to the Passeriformes, 5 species with 66 individuals belonged to the family Sturnidae. The highest diversity was found on bamboo clumps of forest area. Altogether, 14 species were migratory and 25 species were residential bird with a greater number of individuals i.e.,212. Out of 39 species, 12 species with 23 individuals of insectivore bird found in forest area followed by 7 omnivorous species with 36 individuals found in human settlement area.